ENERAPAN MODUL BERBASIS KOMPUTER INTERAKTIF UNTUK MENINGKATKAN KUALITAS PROSES DAN HASIL PEMBELAJARAN PADA MATA KULIAH PNEUMATIK DAN HIDRAULIK - Agung Prijo Budijono; Wahyu Dwi Kurniawan (Faculty of Engineering, Universitas Negeri Yogyakarta, 2012)
ABSTRACTThe Classroom Action Research of the application of computer-based interactive modules with Simulation Software of FluidSIM-P 3 Pneumatic System can be a learning medium for the students to gain the real experience and the concrete work on the hydraulic system. The purpose of this study is to improve the learning quality based on activity description, motivation, response, and learning outcomes. The of data collection techniques were using questionnaire, observation sheets and achievement test. Based on the observation result, the activity of lecturers and students during the learning process Pneumatics and Hydraulics courses,which was using interactive computer-based modules, had improved from the first cycle into the second cycle with the average value of each cycle. The first cycle was observed activity of the lecturers and the students, i.e. 66.63%, and the second cycle was 86.88%. To increase the students’ learning completion from cycle I to cycle II with the percentage oflearning completion in the first cycle was73%, and the second cycle was 100%. Meanwhile the results of the student response tocomputer-based interactive modules of pneumatic and hydraulic was 91.8%.Keywords: modules, interactive, computer, pneumatic, hydraulic